2019
DOI: 10.1002/advs.201902583
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Pulse Stimulation with Ultrasound in Alzheimer's Disease—A New Navigated Focal Brain Therapy

Abstract: Ultrasound‐based brain stimulation techniques may become a powerful new technique to modulate the human brain in a focal and targeted manner. However, for clinical brain stimulation no certified systems exist and the current techniques have to be further developed. Here, a clinical sonication technique is introduced, based on single ultrashort ultrasound pulses (transcranial pulse stimulation, TPS) which markedly differs from existing focused ultrasound techniques. In addition, a first clinical study using ult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
196
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 158 publications
(206 citation statements)
references
References 46 publications
(109 reference statements)
7
196
0
3
Order By: Relevance
“…[51] However, recent technologies have been considerably improved and a novel pulsed stimulation approach has been introduced, which can avoid these dangers (TPS). [41] Extending the previous animal data, the TPS study is also the first to report on minor transient events associated with ultrasound brain stimulation in humans. The authors found rare events of headache (4% of participants), mood deterioration (3%), pain (8%), and painless pressure sensations (17%) in their patient population.…”
Section: Safety Of Transcranial Ultrasound Therapiesmentioning
confidence: 86%
See 4 more Smart Citations
“…[51] However, recent technologies have been considerably improved and a novel pulsed stimulation approach has been introduced, which can avoid these dangers (TPS). [41] Extending the previous animal data, the TPS study is also the first to report on minor transient events associated with ultrasound brain stimulation in humans. The authors found rare events of headache (4% of participants), mood deterioration (3%), pain (8%), and painless pressure sensations (17%) in their patient population.…”
Section: Safety Of Transcranial Ultrasound Therapiesmentioning
confidence: 86%
“…This system applies a different ultrasound technology that is based on single ultrashort ultrasound pulses (transcranial pulse stimulation [TPS]). [41] The pulse durations are not in the millisecond range but the microsecond range (about 3 µs duration), and single pulses are repeated with a frequency between 4 and 8 Hz. Again, every target area is sonicated for several minutes.…”
Section: Brain Stimulation Therapymentioning
confidence: 99%
See 3 more Smart Citations